Bridging XML and Relational Databases: An Effective Mapping Scheme based on Persistent - Samini Subramaniam; Su-Cheng Haw; Poo Kuan Hoong (Institute of Advanced Engineering and Science, 2012)
XML has emerged as the leading medium for data transfer over the World Wide Web. At the present days, relational database is still widely used as the back-end database in most organizations. Since there is mismatch in these two structures, an effective mapping scheme is definitely essential that provides seamless integration with relational databases. On the other hand, an immutable labeling scheme is certainly significant to dentify the XML nodes uniquely as well as supports dynamic update without having the existing labels to be re-labeled when there is an occurance of dynamic update. As such, in this paper, we propose s-XML by adopting the Persistent Labeling scheme as the annotation scheme to ensure seamless integration with relational database and able to support updates without the need to re-construct the existing labels. We conduct experiments to show that s-XML performs better in terms of mapping the XML nodes to relational databases, query retrieval and dynamic update compared to the existing approaches.DOI:http://dx.doi.org/10.11591/ijece.v2i2.215